Acetabular Cup with a Trabecular Coating: A Novel Approach to a Monolithic Cup Made of One High‐Strength Ceramic Material. Issue 10 (1st July 2018) - Adjiski, Ranko; Mühlstädt, Mike; Maenz, Stefan; Arras, Matthias M. L.; Hans, Karen; Ortmann, Claudia; Oberbach, Thomas; Jandt, Klaus D.; Bossert, Jörg
Abstract : An advanced monolithic cup comprising a thin liner and a trabecular coating is a promising alternative to the current modular ceramic cups for hip replacements because it can be anchored directly to the human bone and features larger femoral heads allowing a greater range of motion. In this study, the authors propose a fabrication route for an advanced monolithic cup of only one high‐strength ceramic material by joining a partially sintered liner and a coating with a ceramic paste as an intermediate layer and subsequent sintering. The challenge here is to avoid the formation of defects at the coating/intermediate layer interfaces during classical sintering which is due to compressive tension constrained coating sintering in the initial sintering stages. In this study, the defect formation is minimized by sintering at constant low shrinkage rates, as this results in favorable compressive stresses in the coating in the initial sintering stages and a decrease in the differences in the densification rates. For the first time, by using the proposed route, the authors prepare an advanced monolithic cup of only alumina‐toughened zirconia (ATZ) that contains a coating with a porosity of 50 vol% and interconnected pores between 150 and 450 μm, as required for bone‐ingrowth. Abstract : A method is proposed for the fabrication of advanced monolithic cups only of one high‐strength ceramic material, comprising a green‐state joining of a macroporous coating to a liner with a ceramic paste and sintering. The challenge is to minimize the interfacial defects that adversely affect the adhesion strength, which is realized by sintering at constant low shrinkage rates.